Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/chin.200340233
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method for Evaluating Drug‐Likeness and Ease of Synthesis Using a Data Set in which Compounds Are Assigned Scores Based on Chemists′ Intuition.

Abstract: Intuition. -(TAKAOKA*, Y.; ENDO, Y.; YAMANOBE, S.; KAKINUMA, H.; OKUBO, T.; SHIMAZAKI, Y.; OTA, T.; SUMIYA, S.; YOSHIKAWA, K.; J. Chem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 1 publication
0
41
0
Order By: Relevance
“…In order to develop more reliable prediction models of drug-likeness, a large number of molecular descriptors and numerous machine learning approaches have been employed, such as support vector machine (SVM) [40][41][42][43]67], neural networks (NN) [37,38,40,41,67,68], genetic algorithm (GA) [69][70][71], recursive partitioning (RP) [45,72], etc. Encouragingly, most prediction models for drug-likeness predictions established by machine learning approaches show satisfactory abilities to discriminate between drug-like and non-drug-like molecules.…”
Section: Prediction Models Based On Machine Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop more reliable prediction models of drug-likeness, a large number of molecular descriptors and numerous machine learning approaches have been employed, such as support vector machine (SVM) [40][41][42][43]67], neural networks (NN) [37,38,40,41,67,68], genetic algorithm (GA) [69][70][71], recursive partitioning (RP) [45,72], etc. Encouragingly, most prediction models for drug-likeness predictions established by machine learning approaches show satisfactory abilities to discriminate between drug-like and non-drug-like molecules.…”
Section: Prediction Models Based On Machine Learning Approachesmentioning
confidence: 99%
“…The previous studies showed that the drug-likeness models established by SVM have better prediction accuracies than those established by ANN or RP[40,41,67,72]. In 2003, Takaoka et al built several drug-likeness models based on SVM and ANN [67], and found that the SVM drug-likeness models are superior to the ANN models.…”
mentioning
confidence: 99%
“…2 Current procedures for quantifying synthesizability are based on (1) structure complexity and similarity or (2) synthetic pathways. The structure-based approach usually involves constructing a heuristic definition based on domain expertise or chemical substructure diversity 14,15 or designing a model that can be fit to expert scores [16][17][18] or reaction data. 19,20 This kind of method is widely used due to its ease of implementation and low computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…Computational tools have been developed over the past four decades to help the synthetic chemists (and/or their CADD colleagues) find a viable synthetic route for a novel molecule. They can be broadly categorized into two classes: synthesizability estimation [5][6][7][8][9][10][11][12][13] ; and synthetic route prediction (variously called computer assisted synthesis design (CASD), computer-assisted organic synthesis (CAOS), computer-assisted synthesis planning (CASP), or computer-assisted reaction design (CARD)) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . These tools had their heyday during the 1980s and 1990s but subsequently fell out of favor as an approach used in practice, and the entire field went essentially dormant for a good decade until the field experienced a revival of sorts in the 2010s.…”
Section: Background and Summarymentioning
confidence: 99%